2011
DOI: 10.1177/1947601912440170
|View full text |Cite
|
Sign up to set email alerts
|

Maspin Reprograms the Gene Expression Profile of Prostate Carcinoma Cells for Differentiation

Abstract: Maspin is an epithelial-specific tumor suppressor gene. Previous data suggest that maspin expression may redirect poorly differentiated tumor cells to better differentiated phenotypes. Further, maspin is the first and only endogenous polypeptide inhibitor of histone deacetylase 1 (HDAC1) identified thus far. In the current study, to address what central program of tumor cell redifferentiation is regulated by maspin and how tumor microenvironments further define the effects of maspin, we conducted a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 86 publications
(131 reference statements)
8
70
0
Order By: Relevance
“…These data are in line with the previous data that maspin overexpression suppresses the invasion ability and inhibits the expression of MMP-2 in malignant melanoma cells (33). Although several reports indicate that maspin could target the extracellular uPA/uPAR complex (34,35), which further affects the migration and invasion abilities of certain cancer cells, the expression of uPA/uPAR was not affected by the overexpression of maspin in A549 cells. In the present study, the expression of integrin β1 was downregulated in the maspin-overexpressing A549 cells.…”
Section: Discussionsupporting
confidence: 81%
“…These data are in line with the previous data that maspin overexpression suppresses the invasion ability and inhibits the expression of MMP-2 in malignant melanoma cells (33). Although several reports indicate that maspin could target the extracellular uPA/uPAR complex (34,35), which further affects the migration and invasion abilities of certain cancer cells, the expression of uPA/uPAR was not affected by the overexpression of maspin in A549 cells. In the present study, the expression of integrin β1 was downregulated in the maspin-overexpressing A549 cells.…”
Section: Discussionsupporting
confidence: 81%
“…We have previously shown that maspin, a 42 kDa tumor suppressive endogenous histone deacetylase (HDAC) 1 inhibitor (15, 16), plays a predominant role in the maintenance of the epigenetic program for differentiation (17, 18). Consistently, accumulated experimental evidence showed that maspin exerts multifaceted tumor suppressive effects including reduces tumor cell-associated uPA:uPAR activity (19, 20), blocks tumor cells detachment from established contacts with the extracellular matrix (21), inhibits tumor cell motility and invasion in vitro (17, 22) and inhibits tumor growth and metastasis in xenograft (18) or syngeneic tumor models (23-25).…”
Section: Introductionmentioning
confidence: 99%
“…In normal breast and prostate epithelial cells, maspin is highly expressed and found to be localized mostly in the cytoplasm but has also been detected in the nucleus, secretory vesicles, and occasionally at the cell surface [6][7][8]. Maspin expression is almost completely suppressed in the human prostate cancer LNCaP, DU145, and PC-3 cell lines [9]. At the tissue level, maspin's function seems to be directly correlated with its localization.…”
Section: Expression Of Maspin In Normal Prostate and Cancermentioning
confidence: 81%
“…In benign prostate epithelium, maspin expression is uniformly noted in basal cells at high levels. In contrast, maspin expression is predominantly absent in benign secretory cells and elevated in secretory cells at the transition site between benign prostatic hyperplasia and high-grade PIN lesions [9,10]. Pierson et al noted higher expression of maspin in HGPIN lesions, particularly within secretory cells [11].…”
Section: Expression Of Maspin In Normal Prostate and Cancermentioning
confidence: 96%
See 1 more Smart Citation